Lessons learned from HIV can inform our approach to COVID‐19 stigma - Logie, Carmen H (Journal of the International AIDS Society, 2020)
The arrests of people for breaching COVID‐19 public health measures [ 10] – and subsequent labelling as “intentional murderers” [ 11] and “super spreaders” [ 12] – signal the creation of the “immoral” other. [...]HIV has taught us about the complexity of stigma. Social ecological approaches to HIV remind us that stigma is intrapersonal (affecting our self‐perception and mental health), interpersonal (altering our relationships), social (embedded in community norms and values) and structural (reproduced institutionally in health, legal, employment and other practices) [ 15,16].